Nanotheranostic Applications for Detection and Targeting Neurodegenerative Diseases - Kumar, Ajay; Chaudhary, Ravi Kumar; Singh, Rachita; Singh, Satya P.; Wang, Shao-Yu; Hoe, Zheng-Yu; Pan, Cheng-Tang; Shiue, Yow-Ling; Wei, Dong-Qing; Kaushik, Aman Chandra; Dai, Xiaofeng (Frontiers in Neuroscience, 2020)
Nanotechnology utilizes engineered materials and devices which function with biological systems at the molecular level and could transform the management of neurodegenerative diseases (NDs) by provoking, reacting to and intermingling with target sites to stimulate physiological responses while minimizing side-effects. Blood–brain barrier (BBB) protects the brain from harmful agents and transporting drugs across the BBB is a major challenge for diagnosis, targeting and treatment of neurodegenerative diseases. The BBB provides severe limitations for diagnosis and treatment of Alzheimer disease, Parkinson disease and various other neurological diseases. Conventional drug delivery systems generally fail to cross the BBB, thus are inefficient in treatment. Although gradual development through research is ensuring the progress of nanotheranostic approaches from animal to human modeling, aspects of translational applicability and safety is a key concern. This demands a deep understanding of the interaction of body systems with nanomaterials. There are various plant-based nanobioactive compounds which are reported to have applicability in the diagnosis and treatment of these neurodegenerative diseases. This review article provides an overview of applications of nanotheranostics in Alzheimer’s and Parkinson’s diseases. The review also discusses nano-enabled drug delivery systems and their current and potential applications for the treatment of various neurodegenerative diseases.